C-15 Halogenated Acetogenin with Antibacterial Activity against Food Pathogens - Vairappan, Charles S.; Tan, Kai Lee (Malaysian Journal of Science, 2009)
As part of our continuous effort in search of bioactive secondary metabolites from marine organisms, we studied a specimen of red algae, Laurencia nangii Masuda from Banggi Island, Kudat District, Sabah. One C-15 acetogenin was isolated and identified as Z-dihydrorhodophytin (1, 15%). This compound showed 100% inhibition against the tested bacteria at 30 ïgdisc-1. MIC values for Salmonella enteritidis, Vibrio cholerae and Staphalococcus aereus were 1.25 ïgdisc-1, 2.25 ïgdisc-1 and 2.25 ïgdisc-1, respectively; while Escherichia coli, Salmonella typhii and Salmonella thphymunium were inhibited at MIC value of 7.25 ïgdisc-1. This study showed that Z-dihydrorhodophytin (1) has significant antibacterial activity against the tested food pathogens and may have potential to be used as lead pharmaceutical drug candidate in combating â€œantibiotic resistant bacteriaâ€. Sehubungan dengan usaha kami untuk mengkaji sebatian sekunder bioaktif daripada organisma marin, kami telah menyelidik satu spesimen alga merah, Laurencia nangii Masuda dari Pulau Banggi, Kudat, Sabah. Satu sebatian C15-acetogenin telah dipencilkan dan dikenalpasti sebagai Z-dihydrorhodophytin (1, 15%). Sebatian ini menunjukkan 100% perencatan pada 30 gdisc-1. Nilai MIC bagi Salmonella enteritidis, Vibrio cholerae dan Staphalococcus aereus adalah 1.25 gdisc-1, 2.25 gdisc-1 dan 2.25 gdisc-1, manakala nilai untuk Escherichia coli, Salmonella typhii dan Salmonella thphymunium adalah 7.25 gdisc-1. Kajian ini menunjukkan bahawa Z- dihydrorhodophytin (1) dapat merencatkan bakteria yang diuji dengan signifikan dan mempunyai potensi untuk dijadikan sebagai “lead drug” farmaseutikal dalam usaha mengawal “bakteria rintang antibiotik”.